Plants diversity and socioecological functions of homegarden in Sundanese rural area: A case in Sumedang District, West Java, Indonesia - OPAN S. SUWARTAPRADJA; JOHAN ISKANDAR; BUDIAWATI S. ISKANDAR; DEDE MULYANTO; SUROSO SUROSO; DEDEN NURJAMAN; FEJIH FATHIMAH NISYAPURI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Suwartapradja OS, Iskandar J, Iskandar BS, Mulyanto D, Suroso, Nurjaman D, Nisyapuri FF. 2023. Plants diversity and socioecological functions of homegarden in Sundanese rural area: a case in Sumedang district, West Java, Indonesia. Biodiversitas 24: 156-175. Homegarden is one of the traditional agroforestry systems in Indonesia, which is traditionally planted with various annual and perennial plants. It has provided social, economic, cultural, and ecological functions. The objective of this study is to elucidate the vegetation structure and function of the homegarden system of two groups of rural communities who are affected by the development project of Jatigede Dam, Sumedang, West Java. The first community group of residents who lost their village, their homegarden, and another agricultural land due to the Jatigede dam and settled in new resettlement provided by the local government in Cihegar Mekar Hamlet. The second community group, residents living in the neighboring Kampung Cihegar Mekar, whose settlements and homegarden were not inundated by the Jatigede Dam, but the Jatigede Dam inundated their agricultural lands. Qualitative and quantitative methods were used with an ethnobotanical approach. The results showed that the diversity of species of the homegarden of Cihegar Mekar and Ciboboko Hamlets affected by the Jatigede dam project was high. In Cihegar Hamlet, the number of species, genera, and family in 2018 and 2022 was recorded at 63 and 155, 58 and 130, and 39 and 59, respectively. While in Ciboboko, Hamlet in 2018 and 2022 recorded the number of species, genera, and family at 81 and 144, 76 and 114, and 44 and 55, respectively. These variables have significantly increased in the past 4 years (2018-2022). The residents are intensifying the cultivation of their homegarden because other agricultural land types, such as wet-rice fields, have been dramatically reduced or even lost due to inundation by the Jatigede dam. The 224 plant species found in the homegarden consist of 127 (56.70%), 30 (13.39%), 27 (12.05%), and 13 (5.80%) ornamental, fruit, vegetable, and spice species. At least 20 species and varieties (landraces) of the homegarden have been considered to fulfill the daily household need, and some surpluses are sold to obtain household income. So, the high diversity of plant species in the village homegarden has essential functions to support food security and the population well-being of those affected people of the development project of Jatigede Dam. Homegardens appear to be an important strategy for attaining the rural development program and can be accomplished with proper planning.